ANXIOLYTIC PROFILE OF 5-HT3 ANTAGONIST ONDANSETRON AND ITS CLINICAL CORRELATION - AMITABH A KUMAR,; PADMA SRAVANI,; VISHNU PRIYA, (International Journal of Pharma and Bio Sciences, 2014)
Ondansetron (OND) a popular antiemetic agent mediates its central effect by 5-HT3 antagonism and is used in management of cancer chemotherapy induced nausea and vomiting. There are many studies in literature depicting antianxiety, analgesic and antidepressant effects of drugs modulating serotonergic neurotransmission by 5-HT3 antagonism. This kindled the spirit to evaluate the effect of OND in elevated plus maze (EPM), a popular model to evaluate antianxiety drugs, as there are limited and diverse studies portraying antianxiety effect of OND. In our study, OND demonstrated significant antianxiety activity by increasing the number of entries and duration of stay in open arm as compared to control. The results of our study throw some light to develop novel drugs with different mechanism of action and minimal cognitive adverse effects to elicit anxiolytic effect which may be beneficial to patients with anxiety disorders as drugs acting through serotonergic mechanism do not impair cognitive performance